135
Пошаговое объяснение:
bn = b1 * q^(n-1) - формула n-го члена геом. прогрессии
подставляем в формулу:
b2 = b1 * q^(2-1) = b1 * q = 5
b4 = b1 * q^(4-1) = b1 * q^3 = 15
поделим второе на первое:
(b1 * q^3) / (b1 * q) = 15 / 5
q^2 = 3
q = sqrt(3)
b1 = 5 / q = 5 / sqrt(3)
b8 = b1 * q^(8-1) = b1 * q^7 = (5 / sqrt(3)) * (sqrt(3))^7 = 5 * 3^3 = 135
ответ: 135
b4 / b2 = 15 / 5 = 3
135
Пошаговое объяснение:
bn = b1 * q^(n-1) - формула n-го члена геом. прогрессии
подставляем в формулу:
b2 = b1 * q^(2-1) = b1 * q = 5
b4 = b1 * q^(4-1) = b1 * q^3 = 15
поделим второе на первое:
(b1 * q^3) / (b1 * q) = 15 / 5
q^2 = 3
q = sqrt(3)
b1 = 5 / q = 5 / sqrt(3)
b8 = b1 * q^(8-1) = b1 * q^7 = (5 / sqrt(3)) * (sqrt(3))^7 = 5 * 3^3 = 135
ответ: 135
b4 / b2 = 15 / 5 = 3